Adaptations of the shoulder to overhead throwing in youth athletes - Astolfi, M. M.; Struminger, A. H.; Royer, T. D.; Kaminski, T. W.; Swanik, C. B. (Journal of Athletic Training, 2015)
Context: The high number of repetitions and high forces associated with overhead throwing lead to anatomical adaptations, such as humeral retrotorsion and posterior-capsule thickness, in elite and professional baseball athletes. However, little is known about the origin and progression of these changes that may account for the increasing trend of chronic shoulder injuries in youth baseball and precipitate subsequent pathologic conditions throughout a young athlete's lifetime.